2018
DOI: 10.1186/s12889-018-5184-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns are influenced by socio-demographic conditions of women in childbearing age: a cohort study of pregnant women

Abstract: BackgroundWomen’s health during their reproductive years and whilst pregnant has implications for their children’s health, both in utero and during childhood. Associations of women’s pre-pregnancy dietary patterns (DP) with maternal socio-demographic characteristics and nutrient intake were investigated in ProcriAr cohort study in São Paulo/Brazil, 2012.MethodsThe DPs of 454 women were investigated by principal component factor analysis, using dietary information from a validated 110-item food frequency questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 57 publications
5
28
0
4
Order By: Relevance
“…Considering the sex-related difference in insulin sensitivity, it is clear how sociodemographic aspects may interact with biology [ 61 ]. This association has been observed also in pregnant woman [ 62 ]. Even in the prevention and management of gestational diabetes mellitus, maternal income and education may have a strong impact [ 63 ].…”
Section: Sex Hormones In Endocrine Gender-related Differencessupporting
confidence: 56%
“…Considering the sex-related difference in insulin sensitivity, it is clear how sociodemographic aspects may interact with biology [ 61 ]. This association has been observed also in pregnant woman [ 62 ]. Even in the prevention and management of gestational diabetes mellitus, maternal income and education may have a strong impact [ 63 ].…”
Section: Sex Hormones In Endocrine Gender-related Differencessupporting
confidence: 56%
“…15 The present study demonstrated that the older the maternal age of high-risk pregnant women, the lower the intake of total calories and the percentages of carbohydrates and proteins from ultra-processed foods. This finding agrees with other studies that have shown that older pregnant women tend to eat less unhealthy snacks and fast food, 16,17 which are meals known to increase overweight and obesity 18 as they contain a large amount of sugar, fat and sodium. 19 In the present study, class III obese high-risk pregnant women presented lower percentages of intake of protein from natural/minimally processed foods when compared with overweight or class I and II obese pregnant women.…”
Section: Discussionsupporting
confidence: 92%
“…45 Despite the homogeneous education level of our sample, we observed that women with a higher family income were more likely to adhere to the Prudent pattern, which is in line with the positive association between education (as a proxy of economic status) and adherence to healthy dietary patterns found in other studies. 33,34 In contrast, participants with a lower socioeconomic status (lower family income, lower maternal education, non-white and undergraduates) had a higher probability to adhere to the Brazilian pattern. These findings corroborated studies that had identified inverse associations of the education 32 and family income 34 and direct associations of mulatto skin color 34 with adherence to previously described 'Traditional/Common-Brazilian' patterns.…”
Section: Discussionmentioning
confidence: 95%
“…The Processed pattern was the one that most explained the diet variance and was similar to previously reported in Brazilian adults. [32][33][34] Such patterns have been associated with unfavorable health outcomes, such as type 2 diabetes and cardiovascular disease. 35 Our Prudent pattern resembles those pre-pregnancy pattern named 'seasoned vegetables and lean meats,' 33 or adult's patterns named 'vegetable/fruit,' 32 or 'healthy.'…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation